2000
DOI: 10.1017/s0007114500000143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flavour amplification of Quorn® and yoghurt on food preference and consumption in relation to age, BMI and odour perception

Abstract: Since the food habits of many elderly people are inadequate, the first experiment of the present study tested whether flavour amplification induces changes in preferences for and consumption of food and thus might result in a nutritional benefit. Two panels, one of 260 and one of 120 subjects, aged 19–98 years, took part in the study in which preferences for flavour-amplified yoghurt and Quorn® were measured. For both products, only a few of the young subjects (20 %) preferred the high flavour level; the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…In previous studies, the enhancement of flavour has been reported to be a successful strategy to increase product liking in the elderly (Griep, Mets, & Massart, 1997;Griep, Mets, & Massart, 2000;Mathey, Siebelink, De Graaf, & Van Staveren, 2001;Schiffman & Warwick, 1993). In the present study, the elderlyÕs appreciation was increased by the enhancement of cheese flavour only in the savoury waffles and not for vanilla in the sweet Good ETOC performance Poor ETOC performance Fig.…”
Section: Discussionsupporting
confidence: 55%
“…In previous studies, the enhancement of flavour has been reported to be a successful strategy to increase product liking in the elderly (Griep, Mets, & Massart, 1997;Griep, Mets, & Massart, 2000;Mathey, Siebelink, De Graaf, & Van Staveren, 2001;Schiffman & Warwick, 1993). In the present study, the elderlyÕs appreciation was increased by the enhancement of cheese flavour only in the savoury waffles and not for vanilla in the sweet Good ETOC performance Poor ETOC performance Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Previous research has suggested that older adults may have a higher preferred optimal concentration level for certain flavors or a taste compared with young people (Murphy and Withee 1987;de Graaf et al 1994de Jong et al 1996;Griep et al 2000;Kozlowska et al 2003). We therefore expected that the elderly people with a diminished taste and smell performance would show an increased liking and/or intake of tomato soup enhanced with MSG and celery powder compared with non-enhanced soup.…”
Section: Discussionmentioning
confidence: 95%
“…Generally older adults prefer higher optimal flavor concentrations (by boosting a taste or certain aromas) in a certain number of foods than young people (Murphy and Withee 1987;de Graaf et al 1994de Jong et al 1996;Griep et al 2000;Kozlowska et al 2003). This finding is possibly related to the results found in other studies that enhancing food with flavors and or mono-sodium glutamate (MSG) can increase palatability Warwick 1988, 1993;Schiffman 1998) and intake in the elderly (Mathey et al 2001) and in older adults suffering from malnutrition (Schiffman 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Duffy et al (1999) found that despite normal ability to smell, elderly subjects may have a lower ability to perceive food flavor retronasally. Griep, Mets, and Massart (2000) found that the elderly showing poor performance in odor detection threshold (isoamylacetate) task had no preference for either low or high flavor intensity of food, suggesting that the preference was not associated with olfactory performance. Moreover, Koskinen, Kälviäi-nen, and Tuorila (2003b) found that poor performance in odor detection and identification did not lead to preference for more intense flavor of food.…”
Section: Predictive Ability Of Performance On the Etoc On Retronasal mentioning
confidence: 96%